2016
DOI: 10.3354/meps11697
|View full text |Cite
|
Sign up to set email alerts
|

Mutualistic symbiosis with ophiuroids limited the impact of the Deepwater Horizon oil spill on deep-sea octocorals

Abstract: Deep-water corals form structurally complex biological habitats in the deep-sea that are generally associated with a diverse fauna. Yet, little is known about the effect of symbionts on coral resilience to natural or anthropogenic impacts. This study focused on the influence of the ophiuroid symbiont Asteroschema clavigerum on the resilience of its octocoral host Paramuricea biscaya after the Deepwater Horizon oil spill in the Gulf of Mexico. Corals were imaged between 2011 and 2014 at 4 sites, 3 of which were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 36 publications
(46 reference statements)
0
20
0
Order By: Relevance
“…Moreover, branch loss was still abnormally high seven years after the oil spill, indicating an ongoing effect of the spill on corals . Recovery was influenced by the presence of the ophiuroid associate Asteroschema clavigerum, which facilitated the recovery of impacted corals, likely by removing particles deposited on branches and preventing the settlement of hydroids (Girard et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, branch loss was still abnormally high seven years after the oil spill, indicating an ongoing effect of the spill on corals . Recovery was influenced by the presence of the ophiuroid associate Asteroschema clavigerum, which facilitated the recovery of impacted corals, likely by removing particles deposited on branches and preventing the settlement of hydroids (Girard et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study, however, has suggested that there may be tangible host benefits. Girard et al (2016) studied the relationship between the ophiuroid symbiont Asteroschema clavigerum on the plexaurid octocoral Paramuricea biscaya. They monitored damage and recovery of Paramuricea following the Deepwater Horizon oil spill in the Gulf of Mexico.…”
Section: Symbioses Facilitation and Parasitismmentioning
confidence: 99%
“…Model code and all data used in this study available from the Dryad Digital Repository https://doi.org/10.5061/dryad.2d0g778 (Girard, Shea, & Fisher, ).…”
Section: Data Accessibilitymentioning
confidence: 99%
“…The recovery patterns of impacted coral colonies also varied with the presence or absence of the brittle star (ophiuroid) Asteroschema clavigerum (Verrill, 1894) on the corals. A. clavigerum ophiuroids both provided protection from impact and facilitated recovery of damaged coral branches (Girard, Fu, & Fisher, 2016).…”
Section: Introductionmentioning
confidence: 99%